2014
DOI: 10.12973/eurasia.2014.1120a
|View full text |Cite
|
Sign up to set email alerts
|

A Study on Identifying the Misconceptions of Pre-service and In-service Teachers about Basic Astronomy Concepts

Abstract: Nowadays, the importance given to astronomy teaching in science and physics education has been gradually increasing. At the same time, teachers play an important role in remediating the misconceptions about astronomy concepts held by students. The present study aims to determine the misconceptions of pre-service physics teachers (n=117), preservice science teachers (n=97) and in-service physics teachers (n=174) about astronomy concepts using a three-tier test. The Astronomy Concept and Achievement Test (ACAT),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
34
0
6

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(46 citation statements)
references
References 37 publications
6
34
0
6
Order By: Relevance
“…However, concern about inaccurate estimates still existed. Thus, a three-tier diagnostic instrument was proposed in which the third tier diagnoses students' confidence or certainty of response (Lin, 2016a;Caleon & Subramaniam, 2010;Kanli, 2014;Kirbulut, & Geban, 2014). Researchers in science education have applied the measurement of confidence for several purposes, such as making distinctions between alternative conceptions from either a lack of knowledge or simply guessing.…”
Section: Confidence Assessments To Assist In Identifying Alternative mentioning
confidence: 99%
See 1 more Smart Citation
“…However, concern about inaccurate estimates still existed. Thus, a three-tier diagnostic instrument was proposed in which the third tier diagnoses students' confidence or certainty of response (Lin, 2016a;Caleon & Subramaniam, 2010;Kanli, 2014;Kirbulut, & Geban, 2014). Researchers in science education have applied the measurement of confidence for several purposes, such as making distinctions between alternative conceptions from either a lack of knowledge or simply guessing.…”
Section: Confidence Assessments To Assist In Identifying Alternative mentioning
confidence: 99%
“…They found that students in their study held 21 significant alternative conceptions about waves, of which approximately half were spurious conceptions. Kanli (2014) also used confidence ratings to precisely identify preservice and in-service teachers' basic astronomy conceptions. Accordingly, diagnosing teachers' and learners' confidence in answering questions along with the conceptual diagnostic instruments not only helps researchers identify teachers' and learners' conceptions more accurately but also helps teachers and learners to be aware of their own conceptions.…”
Section: Confidence Assessments To Assist In Identifying Alternative mentioning
confidence: 99%
“…Böylece "Öğretmenlerin alan bilgileri yetersiz olduğunda bu durum öğrencilerine de yansımaktadır" (Alev & Karal, 2013) probleminin çözümünde rol oynayabilecektir. Çünkü yapılan çalışmalar; öğrenciler, öğretmen adayları ve öğretmenlerin Astronomi ve Elektrik konularında eksik ve yetersiz bilgiye hatta kavram yanılgılarına sahip olduklarını vurgulamaktadır (Bektaşlı, 2016;Brunsell & Marcks, 2005;Kaltakçı & Eryılmaz, 2010;Kanlı, 2014;Karal, Alev & Başkan, 2010;Korur, 2015;Küçüközer & Demirci, 2008;Ogan-Bekiroğlu, 2007;Plummer, 2009;Plummer & Maynard, 2014;Sadler et al, 2010;Small & Plummer, 2014;Steinberg & Cormier, 2013;Trumper, 2000;Trundle et al, 2002Trundle et al, , 2006Wilhelm et al, 2007;Ünsal, Güneş & Ergin, 2001). Öğretmenlerin sahip oldukları alan bilgisi kadar, bu süreçte kullandığı öğretim yöntem ve tekniklerinin de önemli büyüktür (Cantrell, Young & Moore, 2003).…”
Section: Tartışma Sonuç Ve öNerilerunclassified
“…However, students are not able to understand targeted topics due to the astronomical topics being abstract, lack of practice, or their instructional focus (Korur, 2015;Steinberg & Cormier, 2013). Not only students but also pre-service teachers and teachers have incomplete and inadequate knowledge or even misconceptions (Bektaşlı, 2016;Brunsell & Marcks, 2005;Emrahoğlu & Öztürk, 2009;İyibil & Sağlam Arslan, 2010;Kalkan & Kıroğlu, 2007;Kanlı, 2014;Korur, 2015;Kurnaz, Gültekin & İyibil, 2013;Ogan-Bekiroğlu, 2007;Plummer, 2009;Plummer & Maynard, 2014;Sadler et al, 2013;Small & Plummer, 2014;Steinberg and Cormier, 2013;Trumper, 2000;Trundle et al, 2002Trundle et al, , 2006Türk et al, 2012;Türkoğlu et al, 2009;Ünsal, Güneş & Ergin 2001;Wilhelm et al, 2007). Misconceptions related to the astronomy among individuals occur during primary education and continue until university years (Ünsal, Güneş & Ergin, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…Looking at the studies done in the field of astronomy, it can be stated that it is on identifying alternative ideas (Goncu & Korur, 2012;Trumper, 2001;Trundle, Atwood & Christopher, 2006;Trundle & Troland, 1996), knowledge level (Bostan, 2008;Kanli, 2014;Kaplan & Ciftci-Tekinarslan, 2013), mental models (Iyibil, 2010;Iyibil & Saglam-Arslan, 2010;Vosniadou & Brewer, 1992;Vosniadou, Skopeliti & Ikospentaki, 2004) and astronomy self-sufficiency (Carter, 2005;Gunes, 2010). Except these, studies investigating the effect of the teaching method on the conceptual understandings/learning effects of individuals on astronomy issues are also available in the national literature.…”
Section: Introductionmentioning
confidence: 99%